Acrobustitis in a Nelore bull: A case report (Research, Society and Development, 2025)
The study aims to report and describe a clinical case of acrobustitis-phimosis in a bull, a disease popularly known as “Formigeiro”, highlighting the importance of early diagnosis and appropriate therapeutic approaches for preserving the animal’s reproductive function and zootechnical performance. The relevance of this study is justified by the significant incidence of this condition in beef herds, especially in Zebu breeds, due to the anatomical characteristics of the prepuce, which favor the development of lesions, inflammation, and complications associated with inadequate hygiene and the high sensitivity of the region. To achieve this objective, a qualitative and descriptive methodology was employed, classified as applied research in the form of a clinical case report. The study involved an adult Nelore bull, approximately six years of age, cared for on a rural property located in the municipality of Cacoal, State of Rondônia, Brazil, belonging to a herd used exclusively for reproduction. The animal presented with preputial edema, purulent discharge, and difficulty protruding the penis. A detailed clinical examination and thorough evaluation of the affected structures led to the diagnosis of acrobustitis. Treatment consisted of a corrective surgical approach, including excision of necrotic tissue, preputial repair, and careful postoperative monitoring. The observed results demonstrated satisfactory recovery, with no recurrences and complete restoration of reproductive function. The efficacy of post-plasty and the importance of early diagnosis in preserving reproductive capacity, animal welfare, and herd productivity are noteworthy.